Media Pembangkit Gelombang Skala Laboratorium - Jamiatul Akmal; Ahmad Suudi; Yoki Surya Grahita; Asnawi Lubis; Novri Tanti; Zulhendri Hasymi (Jurnal Teknik Mesin, 2023)
In the design of offshore building structures, calculations are required by looking at the factors that occur in the ocean. A big factor that occurs is the disturbance force of waves which can disrupt the strength of the building structure to be created. For this reason, this research makes a wave generating media device on a laboratory scale. With this tool, efforts are also made to resemble the original wave, where the deeper it is, the smaller the strength of the wave formed. This effort is an implementation of the wave forms that occur in the open sea. The results of the design of a wave generating media device measuring 3690x830x940 mm. From wave observations and calculations, it was found that the wavelength was 0.5m and the amplitude was 0.01m. It was concluded that the type of wave characteristic produced by this tool was categorized as an airy wave.